Design of flexible PVDF/NaNbO3/RGO nanogenerator and understanding the role of nanofillers in the output voltage signal. (8th September 2017) - Singh, Huidrom Hemojit; Singh, Simrjit; Khare, Neeraj
Abstract: Flexible PVDF/NaNbO3 /RGO thin films have been synthesized and its application in nanogenerator has been explored. In order to understand the effect of the addition of nanofillers NaNbO3 and RGO in PVDF, we have also synthesized and studied PVDF/RGO and PVDF/NaNbO3 nanocomposite films. Even though the β-phase contents are nearly same in the three nanocomposite films, it has been found that the output voltage generated from PVDF/NaNbO3 /RGO nanocomposite film based nanogenerator is maximum (∼2.16 V) with a short circuit current of 0.383 μA. It has been concluded that NaNbO3 nanorods help in the alignment of the electric dipoles in PVDF and also due to the inherent piezoelectric property, it contributes in the overall piezoelectric property of the film. On the other hand presence of RGO helps to move the charges generated inside the film and further allow the dipoles of PVDF to align which leads to enhanced piezoresponse. Graphical abstract: